Perfectionistic Self-Presentation and Suicide in a Young Woman with Major Depression and Psychotic Features - Sabrina Hassan; Gordon L. Flett; Rohan Ganguli; Paul L. Hewitt (Case Reports in Psychiatry)
A woman in her midtwenties with a history of major depressive disorder and a recent major depressive episode with mood-congruent psychotic features died by suicide. Two weeks before her death, she demonstrated exceptional elevations on the nondisplay of imperfection factor of Hewitt and Flett’s Perfectionistic Self-Presentation Scale. Perfectionism and especially perfectionistic self-presentation have been strongly associated with suicide across several populations, accounting for unique variance in suicidality beyond depression and hopelessness. Yet interpersonal facets of perfectionism are not recognized as clinical risk factors for suicide. There is also a paucity of research on perfectionism in relation to psychotic symptoms. This case account illustrates the role of perfectionistic self-presentation in suicides that occur seemingly without warning and, to our knowledge, this is the first examination of perfectionistic self-presentation and suicide in a case where psychotic features occurred. This study, though single case-based, draws attention to perfectionism and perfectionistic self-presentation and their potential roles in suicide, especially when accompanied by other risk factors. Future research in this area may elucidate the role of perfectionism in suicide, singularly and in the context of a comprehensive clinical risk assessment, demonstrating whether perfectionism confers information about suicide risk beyond known clinical risk factors.